Questioning Success in Pediatric Hodgkin Lymphoma - Zubizarreta Pedro (Journal of Public Health International, 2022)
An opinion revisits definitions of success in pediatric Hodgkin lymphoma, balancing survival metrics with late effects and quality of life to inform patient‑centered care.
Keywords: adolescent